2018
DOI: 10.3390/toxins10070300
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Altered Intestinal Microbiota on Chronic Kidney Disease Progression

Abstract: In chronic kidney disease (CKD), accumulation of uremic toxins is associated with an increased risk of CKD progression. Some uremic toxins result from nutrient processing by gut microbiota, yielding precursors of uremic toxins or uremic toxins themselves, such as trimethylamine N-Oxide (TMAO), p-cresyl sulphate, indoxyl sulphate and indole-3 acetic acid. Increased intake of some nutrients may modify the gut microbiota, increasing the number of bacteria that process them to yield uremic toxins. Circulating leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 137 publications
3
84
0
8
Order By: Relevance
“…Increased CKD, increased cardiovascular risk, uremic toxicity, and inflammation are associated with modifications to the microbiota and the subsequent diverse host responses (85). Experimental and clinical data from genomic and nongenomic studies have suggested that an unusual composition of microbiota exists in CKD (7), and preliminary results have suggested that the composition of the microbiota in chronic renal failure patients and early stages of CKD may be altered (87). More recently, the accumulation of uremic toxins was shown to be due to a number of microbiota strains.…”
Section: Gut Microbiome In Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Increased CKD, increased cardiovascular risk, uremic toxicity, and inflammation are associated with modifications to the microbiota and the subsequent diverse host responses (85). Experimental and clinical data from genomic and nongenomic studies have suggested that an unusual composition of microbiota exists in CKD (7), and preliminary results have suggested that the composition of the microbiota in chronic renal failure patients and early stages of CKD may be altered (87). More recently, the accumulation of uremic toxins was shown to be due to a number of microbiota strains.…”
Section: Gut Microbiome In Kidney Diseasementioning
confidence: 99%
“…Many uremic toxins are derived from the absorption of nutrients by gut microbiota, as these nutrients enhance bacterial growth, which in turn produce more uremic toxins. Thus, possible treatments can involve diet modification, changes in microbiota, reducing the production of uremic toxins by microbiota, increasing the excretion of toxins or targeting the removal of certain uremic toxins (7). Of these, diet is the most powerful and easily controlled factor in intestinal microbiota modulation.…”
Section: Polyphenols Microbiota and Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Изучение экологического разнообразия микробного сообщества, согласно индексам альфа-разнообразия Шеннона, показало, что по сравнению со здоровыми лицами, при ХБП на уровне типа увеличено количество протеобактерий, снижено количество фирмикут и актинобактерий, на уровне семейства отмечено увеличение энтеро-и коринобактерий, на уровне рода возрастает количество энтерококков и клостридий. При ХБП доказан повышенный риск прогрессирования болезни при снижении экспрессии генов, связанных с метаболизмом холина, бетаина, L-карнитина, триметиламина-N-оксида (ТМАО) [27].…”
unclassified
“…После трансплантации почки содержание полиаминов в сыворотке крови уменьшается в 3-5 раз [37]. Экспериментальные и клинические исследования, геномные и негеномные, подтвердили развитие дисбиоза при ХБП [27]. Специфические уремические токсины (ТМАО, р-крезол сульфат (PCS), р-крезол глюконид (PCG), индоксил-сульфат (IS), индол-3 ацетоуксусной кислоты (IA), вит.…”
unclassified